Analisis Daya Saing Kopi Indonesia di Pasar Internasional - Yogaswara IG Hamzah; Jabal Tarik Ibrahim; Istis Baroh; Fithri Mufriantie (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2020)
Based on coffee export data 2008-2017, the index value of Indonesia's coffee trade specialization is positive (0-1). The average value of ISPs of Indonesian coffee for 10 years is 0.91, meaning that Indonesia tends to be a coffee exporter country. Indonesian coffee has competitiveness  in the international market with an acceleration ratio value between 10.66 in 2012 to 53.76 in 2008. The always positive acceleration ratio (AR) value shows that Indonesian coffee is able to win the world coffee market. Indonesian coffee also has a comparative advantage with the value of Revealed Comparative Advantages (RCA) which is always positive. The highest RCA value of Indonesian coffee occurred in 2008 at 5.26 and the lowest RCA value in 2011 was 2.60, while the average RCA value of Indonesia was 3.93.